PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MEDAN - Simaremare, Pebri A.; L. Batu, Dyvia Rosa Aprilyanty; Simatupang, Sabar LT; Hutabarat, Lamminar (JURNAL GLOBAL MANAJEMEN, 2023)
his study aims to determine "The Influence of Providing Rewards and Punishments on Employee Performance at the Investment Service and One-Stop Services in Medan City." with a total sample of 57 people. This study uses primary data obtained by distributing questionnaires to employees who work at the Medan City Investment and One-Stop Services Office. Data analysis techniques used in this study were validity, reliability, classical assumption tests, multiple linear regression and hypothesis testing operated by SPSS ver 23 software. Partial testing of the effect of Rewards on Employee Performance obtained a t-count value of 3.243 > t- table 2.005 and has a significant value of 0.002 <0.04 it can be concluded that it has a positive and significant effect on employee performance. Based on the partial test results of the effect of Punishment on Employee Performance, the t-count value is 5.921 > t-table 2.005 and has a significant value of 0.000 <0.05. It can be concluded that Punishment has a positive and significant effect on Employee Performance. Based on the results of the F test count 56,161 > F table 3.17 and have a significant value of 0.000 <0.05 it can be concluded that simultaneously or together have a positive and significant effect on Reward and Punishment on Employee Performance at the Investment Service and One-Stop City Integrated Services Medan. The result of the coefficient of determination R2 is 0.663 or 66.3%, which means that employee performance is influenced by reward and punishment while the remaining 33.7% can be explained by other variables that were not examined in this study. So it can be concluded that Reward and Punishment have a positive influence or jointly on Employee Performance.